Transitional Sex Expression on Some Inflorescence Types and Individual Sex Status in Carica papaya L. - Rachman, Erlin (Proceeding International Conference on Global Resource Conservation, 2013)
Flower buds of some inflorescence types of papaya (Carica papaya L.) were studied to know the sexual phenomena in the species. We distinguished six normal and transitional sex expressions in flower buds: normal stamens but no pistil, called normal male, a normal pistil but no stamen called normal female, normal stamens gathered with a normal pistil called normal hermaphrodite, normal stamens gathered with incomplete pistil called transitional hermaphrodite, an incomplete pistil only without stamen called transitional female, and normal stamens gathered with a rudiment spearhead-like pistil called transitional hermaphrodite The bud age levels were defined by bud sizes, from smallest to largest just before the flower anthesis. Transitional pistil was also microscopically distinguishable from normal one. Transitional pistil frequencies significantly tend to be decreased in late flower development phases. Average frequencies of the flower bud sex expression were respectively 16.77, 14.55, 25.81, 27.36, 8.30 and 7.86. Hermaphrodite flower buds showed higher transitional bud frequency than pistilate flower. Most of the transitional buds were shed in its later development and may be eliminated at all in mature inflorescences. It may be the process by which the individual become stable male papaya tree. The involvement of evolutionary primitive Y chromosome on determining male sex expression in the papaya flower growth and development is also discussed. Keywords: Carica papaya L, flowering biology, hermaphrodite, pistilate, staminate, sexual status, transitional sex expression